FINANCIAL EQUALIZATION OF TERRITORIAL DEVELOPMENT EAST EUROPEAN COUNTRIES AND ITS IMPACT ON QUALITY OF LIFE - Olena Ivanenko (Center for Quality, Faculty of Engineering, University of Kragujevac, Serbia, 2021)
Financial equalization of the development of the territories of Eastern European countries directly depends on the order of distribution of functions between public entities and the order of distribution of expenditures between states and individual territories. The studied countries of Eastern Europe belong to the less developed regions, whose GDP per capita is less than 75% of the EU average GDP. In the countries of Eastern Europe financial equalization is mainly based both on the functioning of funds (as an instrument of inter-budgetary balancing) and based on the analysis of tax revenues and expenditures of the territory. The dependence between equalization of expenditures of territories and socio-economic characteristics of their development. However, it is established that the quality of life is not significantly affected by financial subsidies. Improving the efficiency of the use of financial resources to increase the quality of life may be promising for further research.